2023
DOI: 10.1093/toxsci/kfad080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reproducibility and robustness of a renal proximal tubule microphysiological system OrganoPlate 3-lane 40 for in vitro studies of drug transport and toxicity

Abstract: Microphysiological systems are an emerging area of in vitro drug development, and their independent evaluation is important for wide adoption and use. The primary goal of this study was to test reproducibility and robustness of a renal proximal tubule microphysiological system, OrganoPlate® 3-lane 40, as an in vitro model for drug transport and toxicity studies. This microfluidic model was compared to static multi-well cultures and tested using several human renal proximal tubule epithelial cell (RPTEC) types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…For instance, primary PTEC have been demonstrated to exhibit probenecid-inhibitable PAH transepithelial transport in an MPS device but not when maintained under static conditions [52]. However, other studies have shown that MPS systems did not improve OAT functionality [42,53]. Nevertheless, MPS systems could offer a promising avenue for further exploration for such studies, including improving the differentiated phenotype of iPSC-derived PTL.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, primary PTEC have been demonstrated to exhibit probenecid-inhibitable PAH transepithelial transport in an MPS device but not when maintained under static conditions [52]. However, other studies have shown that MPS systems did not improve OAT functionality [42,53]. Nevertheless, MPS systems could offer a promising avenue for further exploration for such studies, including improving the differentiated phenotype of iPSC-derived PTL.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue chip testing centres established by the NIH National Center for Advancing Translational Sciences initiated grantees to validate various types of tissue chip platforms for drug testing 566 , 567 . Under these grants, three independent organisations validated microphysiological systems that replicated the kidney, liver, and BBB for drug transport and toxicity studies, with the goal of increasing the reliability, reproducibility, robustness, and throughput of its effective application 568 .…”
Section: The Outlook Of In Vitro Model In the Pharmacological Industrymentioning
confidence: 99%